2020
DOI: 10.1093/scan/nsaa158
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of prefrontal tDCS on inhibitory control and reactive aggression

Abstract: Increased aggression and impulsivity represent a key component of several psychiatric disorders, including substance use disorder, which is often associated with deficient prefrontal brain activation. Thus, innovative tools to increase cognitive control are highly warranted. The current study investigates the potential of transcranial direct current stimulation (tDCS), a tool to modulate cortical activation, to increase cognitive control in individuals with a high potential for impulsive and agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 58 publications
4
32
1
Order By: Relevance
“…However, it should be noted that significant inter-individual variability in executive performance in response to prefrontal tDCS exists. A recent study by Weidler et al [83] found evidence for this, wherein the upregulation of right DLPFC improved response inhibition performance among alcohol and tobacco-dependent patients in the stopsignal task administered 40 min after the stimulation as opposed to healthy controls (characterized by lower impulsivity traits).…”
Section: Discussionmentioning
confidence: 95%
“…However, it should be noted that significant inter-individual variability in executive performance in response to prefrontal tDCS exists. A recent study by Weidler et al [83] found evidence for this, wherein the upregulation of right DLPFC improved response inhibition performance among alcohol and tobacco-dependent patients in the stopsignal task administered 40 min after the stimulation as opposed to healthy controls (characterized by lower impulsivity traits).…”
Section: Discussionmentioning
confidence: 95%
“…Several studies documented a relation between alcohol consumption and aggressive crimes, such as homicides, assaults, and rapes [84][85][86][87]. tDCS modulated aggressive behavior in a male sample of Alcohol-Dependent (AD) patients [88]. After a-tDCS stimulation…”
Section: Agg Re Ss Ivene Ss Impul S Ivit Y Clini C Alcond Iti On S An...mentioning
confidence: 99%
“…Furthermore, many studies have enrolled male participants only, making it impossible to investigate potential gender effects [88,90,94,96]. Further methodological limitations concern the single tDCS sessions and absence of follow-up measures [30,33,39,41,46,48,52,88]; indeed, given that the literature focuses on the acute effects of the stimulation (i.e., immediately after the stimulation), no evidence is available for the long-term effects. In addition, limited sample sizes (approximately 30 participants) might represent an obstacle for results generalization [21,33,39,41].…”
Section: Limitsandfutureper S Pec Tive Smentioning
confidence: 99%
See 2 more Smart Citations